A Randomised Controlled Trial of Treatment for Post-Stroke Homonymous Hemianopia: Screening and Recruitment. (2nd January 2016) - Rowe, Fiona J.; Conroy, Elizabeth J.; Barton, P. Graham; Bedson, Emma; Cwiklinski, Emma; Dodridge, Caroline; Drummond, Avril; Garcia-Finana, Marta; Howard, Claire; Johnson, Stevie; MacIntosh, Claire; Noonan, Carmel P.; et al.
ABSTRACT: The authors report the screening process and recruitment figures for the VISION (Visual Impairment in Stroke; Intervention Or Not) trial. This is a prospective, randomised, single-blinded, three-arm controlled trial in 14 UK acute hospital stroke units. Stroke teams identified stroke survivors suspected as having homonymous hemianopia. Interventions included Fresnel prisms versus visual search training versus standard care (information only). Primary outcome was change in visual field assessment from baseline to 26 weeks. Secondary measures included change in quality-of-life questionnaires. Recruitment opened in May 2011. A total of 1171 patients were screened by the local principal investigators. Of 1171 patients, 178 (15.2%) were eligible for recruitment: 87 patients (7.4%) provided consent and were recruited; 91 patients (7.8%) did not provide consent, and 993 of 1171 patients (84.8%) failed to meet the eligibility criteria. Almost half were excluded due to complete/partial recovery of hemianopia (43.6%; n = 511). The most common ineligibility reason was recovery of hemianopia. When designing future trials in this area, changes in eligibility criteria/outcome selection to allow more patients to be recruited should be considered, e.g., less stringent levels of visual acuity/refractive error. Alternative outcomes measurable in the home environment, rather than requiring hospital attendance for follow-up, could facilitate increased recruitment.